Post-Newtonian analysis of a precessing convention for spinning compact binaries. (4th August 2015) - Gupta, A; Gopakumar, A
Abstract: A precessing source frame, constructed using the Newtonian orbital angular momentum, can be invoked to model inspiral gravitational waves from generic spinning compact binaries. An attractive feature of such a precessing convention is its ability to remove all spin precession induced modulations from the orbital phase evolution. However, this convention usually employs a post-Newtonian (PN) accurate precessional equation, appropriate for the PN accurate orbital angular momentum, to evolve the -based precessing source frame. This influenced us to develop inspiral waveforms for spinning compact binaries in a precessing convention that explicitly employ to describe the binary orbits. Our approach introduces certain additional 3PN order terms in the evolution equations for the orbital phase and frequency with respect to the usual -based implementation of the precessing convention. We examine the practical implications of these additional terms by computing the match between inspiral waveforms that employ and -based precessing conventions. The match estimates are found to be smaller than the optimal value, namely 0.97, for a non-negligible fraction of unequal mass spinning compact binaries.